RASIO KEUANGAN SEBAGAI PREDIKATOR LABA DIMASA YANG AKAN DATANG (Students' Journal of Accounting and Banking, 2012)
The purpose of this research is to know the influence of profit changes, changes receivable, changes in inventories, changes in the cost of administration and sales, gross profit on sales changes to predict profit a year ahead on the manufacturing company that listed on the Indonesia stock exchange (IDX).This research using a sample of as many as 48 to win the manufacturing company profit on each annual period. selected by using the method of purposive sampling and use of secondary data in the form of financial statements and auditan income statement period 2008-2010 in manufacturing companies listed on the Indonesia stock exchange (IDX), Regression Analysis used to test the hypothesis. The results showed that the variable profit and gross profit on the sale of influential positive future profits against to come, whereas the variable receivable, inventory, accounts Sales and Administration Costs have no effect against future profits to come.Keywords: Pofit, receivable, Inventory, Cost Administration and Sale, Gross Profit on Sale.